1988
DOI: 10.1111/j.2042-3306.1988.tb01542.x
|View full text |Cite
|
Sign up to set email alerts
|

The gait of pacers 1: kinematics of the racing stride

Abstract: Summary Standardbred pacers have been studied under race conditions to describe the gait of the pacer, and to determine relationships between stage of the race, finish order and selected gait kinematics. Overlap increased with the stage of the race while pacing speed decreased marginally for low order pacers and increased for high order finishers. High order finishing pacers appear to have greater stance and stride lengths than do low order finishers. Pacers could be separated into low order and high order gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
1
10
1
Order By: Relevance
“…The values for foot-fall timings measured here are similar to previously published values of walk (Witte et al, 2004), tolt (Zips et al, 2001;Nicodemus and Clayton, 2003;Biknevicius et al, 2004), trot (Drevemo et al, 1980a;Drevemo et al, 1980b;Drevemo et al, 1980c;Clayton, 1994a), pace (Wilson et al, 1987a) and gallop (Hildebrand, 1959;Deuel and Lawrence, 1986;Clayton, 1994b;Back et al, 1997) in horses.…”
Section: Experimental Findings Stride Variablessupporting
confidence: 77%
“…The values for foot-fall timings measured here are similar to previously published values of walk (Witte et al, 2004), tolt (Zips et al, 2001;Nicodemus and Clayton, 2003;Biknevicius et al, 2004), trot (Drevemo et al, 1980a;Drevemo et al, 1980b;Drevemo et al, 1980c;Clayton, 1994a), pace (Wilson et al, 1987a) and gallop (Hildebrand, 1959;Deuel and Lawrence, 1986;Clayton, 1994b;Back et al, 1997) in horses.…”
Section: Experimental Findings Stride Variablessupporting
confidence: 77%
“…Since these four laps were run by two horses with and without weights, the preference of the fore-over the hindlimbs could be due to the individual footfall pattern of these horses rather than to the speed. These findings contrast those found in the literature for Standardbred pacers, where it was stated, that the hindlimbs tend to stay on the ground longer than the forelimbs, especially in high order finishing individuals (Wilson et al 1988a, Wilson et al 1988b. A study performed using Icelandic Horses also found that the stance time of the hindlimbs was longer than that of the forelimbs, but they also noted a considerable variation in fore-and hindlimb ratios and that the values for the stance times and ratios were more variable in the hindlimbs (Robilliard et al 2007).…”
Section: Discussioncontrasting
confidence: 57%
“…Two studies dealt with the racing gait of Standardbred pacers in order to determine factors influencing the racing speed (Wilson et al 1988a, Wilson et al 1988b). The effects of the weight of the shoeing and changes in hoof length were the topic of another study of interest (Balch et al 1996), and one tested the influence of the shoeing on kinematic parameters (Singleton et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, analyses bases on high-speed film recordings are time consuming due to the tedious manual or semimanual tracking of marker positions. Consequently, most studies have been limited to analyses of basic intra-and/or inter limb variables [2][3][4][5][6]. With introduction of the TrackEye system, the tracking procedure can be speeded up consid erably.…”
Section: Discussionmentioning
confidence: 99%
“…which permit recordings of fast movements with good time and linear resolution |l |. The recordings are usually performed with one camera from the side or front of the horse, thereby giving a two-dimensional image, and the analyses have mainly comprised basic time and linear vari ables [2][3][4][5][6], The major disadvantage with this technique is the tedious manual frame-by-frame digitization of the ref erence markers fixed to the horse.…”
Section: Introductionmentioning
confidence: 99%